2020
DOI: 10.3389/fbioe.2020.581621
|View full text |Cite
|
Sign up to set email alerts
|

Pranoprofen Nanoparticles With Poly(L-Lactide)-b-Poly(Ethylene Glycol)-b-Poly(L-Lactide) as the Matrix Toward Improving Ocular Anti-inflammation

Abstract: Nanotechnology using biodegradable polymer carriers with good biocompatibility and bioabsorbability has been studied and applied extensively in drug delivery systems and biomedical engineering. In this work, the triblocked oligomer poly(L-lactide)-bpoly(ethylene glycol)-b-poly(L-lactide) (PLEL) with the molecular weight of 2.08 KDa was first synthesized. Its chemistry was characterized by hydrogen nuclear magnetic resonance (1 H-NMR) spectrum and Fourier transform infrared (FTIR) spectroscopy. Subsequently, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…By contrast with the administration of the free drugs (NAT and CLZ), the sustained release from the core-shell NPs demonstrates that the developed NPs can be used as an important platform for continuous drug release. This characteristic is expected to prove very useful in providing long-lasting anti-inflammatory effects with low administration frequency ( Luo et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast with the administration of the free drugs (NAT and CLZ), the sustained release from the core-shell NPs demonstrates that the developed NPs can be used as an important platform for continuous drug release. This characteristic is expected to prove very useful in providing long-lasting anti-inflammatory effects with low administration frequency ( Luo et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…3 The degradation products are metabolised via the Krebs cycle and cleared by the body 4 and several studies have reported their biocompatibility in many biological tissues. 1,[4][5][6][7][8] There are many examples in the literature using PLGA-based materials for delivery of therapeutics to promote either fast or prolonged drug release with applications in cancer treatment, pain management, immunotherapy, and more recently, in the treatment of pulmonary tuberculosis, urinary tract infections, migraine and glaucoma. 5,6,[9][10][11][12][13][14][15] There are several techniques that are used for the preparation of PLGA particles including single and double emulsion solvent evaporation (ESE), nanoprecipitation, spray-drying, microfluidics, and hydrogel templating.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Thus, results implied that polymeric nanoparticles of Eudragit RL 100 would be having higher structural stability and conserve their integrity upon extreme dilution in biological milieu. [25,38] Polymeric coating over bromelain in Br-EuNCs hindered the penetration of dissolution medium in matrix and promoted prolonged release of drug from polymeric matrix. The results of mucoadhesion study demonstrated that Br-EuNCs had higher mucoadhesive property due to the electrostatic interactions between the positively charged ammonium group of Eudragit RL100 and negatively charged domains of the mucin chains.…”
Section: Discussionmentioning
confidence: 97%